2017
DOI: 10.1097/pas.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression and Intratumoral Heterogeneity Across Breast Cancer Subtypes and Stages

Abstract: Tumor expression of programmed cell death ligand 1 (PD-L1) is associated with immune evasion in a variety of malignancies, including a subset of triple-negative breast carcinomas, and may mark cancers as susceptible to PD-1/PD-L1 inhibitor therapies. We herein characterize PD-L1 expression in breast cancers across the full range of histomorphologies and investigate its intratumoral heterogeneity and fidelity across primaries and metastases. A total of 245 primary and 40 metastatic (20 nodal, 20 distant) breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
130
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 33 publications
13
130
0
3
Order By: Relevance
“…In addition, it has been reported that PD‐L1 is differentially expressed across different BC subtypes. In particular, available evidence consistently reports greater expression of PD‐L1 in the TN subtype (up to 60% of PD‐L1 expression) compared with non‐TNBC . These data appear to be coherent with the observation that PD‐L1 tumor expression is positively associated with stromal tumor‐infiltrating lymphocytes (TILs) in this BC subtype , which is known to be more frequently infiltrated by stromal TILs than non‐TNBC , as summarized in Table , thus possibly suggesting that these two immune biomarkers tend to run parallel.…”
Section: Methodssupporting
confidence: 74%
See 4 more Smart Citations
“…In addition, it has been reported that PD‐L1 is differentially expressed across different BC subtypes. In particular, available evidence consistently reports greater expression of PD‐L1 in the TN subtype (up to 60% of PD‐L1 expression) compared with non‐TNBC . These data appear to be coherent with the observation that PD‐L1 tumor expression is positively associated with stromal tumor‐infiltrating lymphocytes (TILs) in this BC subtype , which is known to be more frequently infiltrated by stromal TILs than non‐TNBC , as summarized in Table , thus possibly suggesting that these two immune biomarkers tend to run parallel.…”
Section: Methodssupporting
confidence: 74%
“…Data on PD‐L1 expression in HER2‐positive BC are more controversial. In fact, whereas in some studies HER2 positivity has been correlated with higher expression of PD‐L1 (up to 50%) compared with HER2‐negative BC , others failed to report any difference .…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations